The Dynamics of Gossip Among Qur’an Memorizers: A Sociological Study of Gawagis, Nawaning, and Local Santri - Nala Rahmatul Izza; Rosyida Amalia; Eko Prasetyo Budi (AN NUR: Jurnal Studi Islam, 2026)
Qur’an Memorization Is Generally Perceived As An Individual Spiritual Practice. Nevertheless, In The Context Of Tahfiz Communities, This Activity Is Conducted Within A Social Environment Where Interaction, Assessment, And Everyday Communication Continuously Take Place. Among These Interactions, Gossip Emerges As An Informal Mode Of Communication That Contributes To The Shaping Of Social Experiences Among Qur’an Memorizers. This Study Was Undertaken To Analyze The Dynamics Of Gossip By Examining Its Forms, The Social Circumstances That Enable Its Occurrence, And Its Implications For Social Relations And The Memorization Process. A Qualitative Research Design Grounded In A Sociological Perspective Was Applied. Data Were Gathered Through In-Depth Interviews, Non-Participant Observation, And The Examination Of Relevant Documents. The Data Were Then Processed Through Thematic Analysis. The Findings Reveal That Gossip Is Expressed In Various Forms, Including Discussions Related To Moral Conduct, Memorization Performance, And Interpersonal Relations. These Practices Operate As Informal Social Mechanisms Through Which Community Norms, Social Relationships, And Symbolic Positions Are Formed And Maintained Among Gawagis, Nawaning, And Local Santri. Furthermore, Gossip Is Shown To Affect Individual Motivation, Patterns Of Social Interaction, And The Distribution Of Symbolic Recognition Within The Tahfiz Community. This Study Offers A Sociological Contribution To Studies On Qur’an Memorization By Highlighting Gossip As A Social Practice That Influences Learning Experiences, Relational Dynamics, And Symbolic Structures Within Religious Communities.